Frontiers in Clinical Neurosurgery - Lv, Xianli; Wang, Guihuai; Wang, James; Wu, Zhongxue (IntechOpen, 2021)
Neurosurgery is a fascinating surgical specialty that has undergone fundamental changes. Fifty years ago, microsurgery technology was just introduced into neurosurgery. At that time, CT and MRI technology had not yet been developed. The treatment of intracranial aneurysms and cerebrovascular malformations was still at a primitive level. Radiosurgery, neuroendoscopic technology, and computer-guided navigation only became popular for the treatment of central nervous system diseases during the last three decades. Today, neurosurgery has entered the stage of minimally invasive neurosurgery. This book provides a clear and concise review of new concepts in neurosurgery, including medical humanism in neurosurgery, functional neuroimaging, neuroendoscopy, and much more. It is a useful resource for medical students, residents, fellows, professors, and researchers in the field.